Pelatihan Good Farming Practises, dan Good Manufacturing Practises untuk Meningkatkan Daya Saing UKM Abinisa Serang Banten - Zakiah Wulandari; Niken Ulupi; Irma Isnafia Arief; Siti Aminah; Teuku Muhammad Alfiansyah; Muhammad Rifqi Mauludi; Qorina Alifiya; Yosua Kristianto Silaban (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
UKM Abinisa is a leading producer in the duck egg processing industry in Serang, Banten. To maintain competitiveness, SME need to focus on product innovation and implement Good Manufacturing Practices (GMP) and Good Farming Practices (GFP) to ensure product safety. This community service program aimed to provide training related to GMP and GFP. Socialization and training activities were held on the same date in Sujung Village, Tirtayasa Subdistrict, Serang Regency, Banten. The steps of the activity included: a) pre-activity preparation, b) internal coordination, c) implementation, and d) evaluation. The activity began with a visit to a duck farm owned by one of UKM Abinisa's farmer partners. The first training session covered techniques for proper and effective feeding, disease prevention, and maintaining healthy living conditions for ducks. Practical sessions included duck herding or releasing them onto post-harvest rice fields, a method well-suited to the extensive rice fields around Sujung Village. This method is known as the rice-duck integration system. The evaluation results showed a high level of participant satisfaction, with the highest-rated material being Material 1: Duck Farming, scoring 69.57%. Material 3 scored similarly at 65.22%. Material 2: Introduction to GMP received the lowest score, likely because of the complexity and detailed nature of the regulations, which were unfamiliar to all participants.